2016
DOI: 10.1002/2211-5463.12058
|View full text |Cite
|
Sign up to set email alerts
|

MafB deficiency accelerates the development of obesity in mice

Abstract: MafB, a transcription factor expressed selectively in macrophages, has important roles in some macrophage‐related diseases, especially in atherosclerosis. In this study, we investigated the mechanism by which hematopoietic‐specific MafB deficiency induces the development of obesity. Wild‐type and hematopoietic cell‐specific Mafb ‐deficient mice were fed a high‐fat diet for 10 weeks. The Mafb ‐deficient mice exhibited higher body weights and faster rates of body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…This discrepancy may reflect the use of mice with different genetic backgrounds in the present study, whereas the difference in the Cre drivers used is unlikely to have contributed, because we also generated a Mafb conditional-knockout mouse with Pdx1-Cre (24), which exhibited the same phenotype as Mafb ⌬Endo mice (data not shown). Indeed, the Mafb f/f mice used in the present study (25,26) and by Conrad et al (10,27) were generated in mouse embryonic stem (ES) cells from different genetic backgrounds, e.g., C57BL/6J and 129S4/SvJae, which may explain the phenotypic variations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This discrepancy may reflect the use of mice with different genetic backgrounds in the present study, whereas the difference in the Cre drivers used is unlikely to have contributed, because we also generated a Mafb conditional-knockout mouse with Pdx1-Cre (24), which exhibited the same phenotype as Mafb ⌬Endo mice (data not shown). Indeed, the Mafb f/f mice used in the present study (25,26) and by Conrad et al (10,27) were generated in mouse embryonic stem (ES) cells from different genetic backgrounds, e.g., C57BL/6J and 129S4/SvJae, which may explain the phenotypic variations.…”
Section: Discussionmentioning
confidence: 93%
“…All animal experiments were approved by the Institutional Animal Care and Use Committee of the University of Tsukuba. Endocrine cell-specific and TAM-dependent Mafb knockout mice were generated by crossing Mafb f/f mice (25,26) with either Ngn3-Cre (52) or CAGG-CreER (stock number 004682; The Jackson Laboratory) (53) transgenic mice. Mafb f/f mice were generated in a C57BL/6J strain background, as described previously (25,26).…”
Section: Methodsmentioning
confidence: 99%
“…Under these conditions, the size and weight of white adipose tissue increased, and AIM inhibited fat synthesis after uptake by adipocytes. As a reduction in AIM expression was observed in the adipose tissue macrophages of Mafbdeficient mice, AIM reduction may be the cause of obesity in Mafb-deficient mice [73]. another recent report demonstrated that after inducing ischemic stroke, macrophage-specific Mafb-deficient mice (Mafb f/f ::LysM-Cre) showed excessive inflammation.…”
Section: The Phenotype Of Mafb-deficient Macrophages and Mafb Target mentioning
confidence: 98%
“…MAFB also links to the metabolism and development of obesity and diabetes. The MAFB-deficient mice exhibited higher body weights and faster rates of body weight increase than control mice [26]. Up-regulation of MAFB expression in human adipocytes is correlated with adverse metabolic features and inflammation which may lead to the development of 10 insulin resistance [27].…”
Section: Supervised Classification Of Genes Expression Discriminate Dmentioning
confidence: 99%